Determinasi Return on Asset, Leverage, Ukuran Perusahaan, Kompensasi Rugi Fiskal dan Kepemilikan Institusi Terhadap Penghindaran Pajak: Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011 - 2014 - Saifudin, Saifudin; Yunanda, Derick (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
This study was conducted to examine the relationship between variables contained on factors affecting Manufacturing Company Taxation in Period 2011-2014. The sampling technique used is pusposive sampling and the number of samples used were 140 corporate data. The variables used in this study, namely tax evasion as the dependent variable and the return on assets, leverage, company size, Tax Loss Compensation and Ownership Institution. The analysis technique used is multiple regression and hypothesis testing using t statistics to test the partial regression coefficient and F-statistic to test the effect together with a confidence level of 5%. The results showed that the variables Profitability and Compensation Tax Loss has significant influence with tax evasion. While other variables do not have a significant relationship with tax evasion. Of Adjusted R2 value of 0.139 indicates that the independent variables that exist in the model can explain the variation (fluctuation) of tax evasion amounting to 13.9%, while 86.1% of the variation of tax avoidance is explained by other variables outside the model.